2005
DOI: 10.1159/000084163
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamine Levels after Fluoxetine Treatment in Depressive Patients

Abstract: It is known that selective serotonin reuptake inhibitors, widely used as antidepressive drugs, act by inhibiting the cell reuptake of serotonin, but their effect on the catecholaminergic system is not yet completely understood. In this study, we investigated plasma concentrations of norepinephrine, epinephrine and dopamine after acute and chronic administration of fluoxetine in depressive patients. Twelve patients affected by major depression received a single oral dose of fluoxetine in the morning, 5 mg in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Similar to the findings in healthy humans, fluoxetine resulted in an increased response of cortisol during hypoglycemia. This also demon- strates that the SSRI was having effects to activate multiple neural pathways within the central nervous system (7). Accompanying the amplified SNS responses were significant increases in blood pressure and heart rate during hypoglycemia following fluoxetine.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to the findings in healthy humans, fluoxetine resulted in an increased response of cortisol during hypoglycemia. This also demon- strates that the SSRI was having effects to activate multiple neural pathways within the central nervous system (7). Accompanying the amplified SNS responses were significant increases in blood pressure and heart rate during hypoglycemia following fluoxetine.…”
Section: Discussionmentioning
confidence: 79%
“…Fluoxetine markedly enhanced COX-1 expression, while ranitidine did not improve COX-1 in both models of ulcer induction. This could be explained by an ability of fluoxetine to increase plasma adrenaline (Blardi et al 2005) that, in turn, is able to increase COX-1 levels in gastric tissue by stimulating 2 receptors (Suleyman et al 2009b). The current results also showed that fluoxetine increased expression of COX-2 in both models, a finding in agreement with a previous study wherein fluoxetine up-regulated brain COX-2 expression (Wang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The neural mechanisms responsible for fluoxetine's effects on amplifying counterregulatory responses to hypoglycemia are not evident from this study. Numerous studies have demonstrated interactions between serotonergic (both 5-HT1A and 5-HT3) and catecholamine neurotransmission pathways in multiple areas of the brain (8). These include forebrain (thalamus and hypothalamus) and hindbrain nuclei that are known to play important roles in regulating ANS responses during hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, although SSRIs are potent inhibitors of neuronal serotonin uptake, they also have the ability to block norepinephrine transport (7). This could increase sympathetic outflow activity (2,8). Baudrie and Chaouloff (9) have previously reported an increased hyperglycemic response to 2-deoxy-D-glycose in conscious rats following serotononergic receptor antagonists, implying increased counterregulation in these animals.…”
mentioning
confidence: 99%